PLANNING OF THE SANITARY LANDFILL SYSTEM IN SURAKARTA CITY - David Anwar; Rosslan Edy Santosa (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2020)
Waste processing sites have a sueful life, as the activities and populations increase in the Surakarta City has led to increasing volume of the garbage that come to landfill every day. Putri Cempo’s Landfill operation system still uses the conventional system, called open dumping. This system causes accumulation of garbage increasingly mountainous and not polluted. Therefore, a system called sanitary landfill is planned to increase landfill capacity and extend the life of landfill.The purpose of this final project is to plan the development of landfill in Surakarta City with a sanitary landfill system. This development is made by making landfill cell in lieu of the open dumping system. The method of landfill cell waste using the trench method to further optimize landfill cell land.The development of TPA using a sanitary landfill was carried out in an area of 6.7 Ha. With the prediction of the amount of waste entering the landfill in 2026 around 15.041 tons/year. The age of using landfill is predicted to range from 5 years and the drainage size used is 50x50 and 100x50 made from river stone for around the landfill and made from precast cell for around the facilities building